Endothelin-1 and Endothelin Converting Enzyme-1 in Human Atherosclerosis - Novel Targets for Pharmacotherapy in Atherosclerosis - Ihling, C.; Bohrmann, B.; Schaefer, H. E.; Technau-Ihling, K.; Loeffler, B. M. (Current Vascular Pharmacology, 2004)
The role of chronic inflammation in the pathogenesis of the acute coronary syndromes has received increasing attention since active plaques rich in macrophages (MfΦs) are more prone to rupture whereas plaques rich in myofibroblasts are considered to be stable. Functionally, active plaques show a locally enhanced vasoreactivity. Endothelin-1 (ET-1) a potent vasoconstrictor acts in a paracrine fashion to regulate vascular tone. ET-1 is also produced by inflammatory cells suggesting a role for ET-1 in inflammation. Additionally, ET-1 is a mitogen. Endothelin converting enzyme-1 (ECE-1) activates ET-1 and may thus contribute to the regulation of vascular tone and cell growth during atherosclerosis. We evaluated the presence of ECE-1 and big ET-1 / ET-1 and the activity of ECE-1 in different plaque types. Together with ET-1, ECE-1 is present in endothelial cells (ECs), vascular smooth muscle cells (VSMCs) and MfΦs. ECE-1 activity and ET-1-immunoreactivity (IR) both are upregulated during the progression of atherosclerosis from a non-inflammatory to an inflammatory stage. Thus, enhanced production of active ET-1 may contribute to cell growth and regulation of vascular tone in advanced plaques and also in very early stages of atherosclerosis. Furthermore, we examined the presence of ET-1 in coronary plaque tissue obtained by directional coronary atherectomy. ET-1 IR localized to plaque components indicative of chronic inflammation. Semiquantitative analysis of ET-1 IR revealed significantly higher staining grades in active coronary lesions compared with nonactive lesions. The increased ET-1 content in active coronary lesions may be beneficial to the stabilization of the vessel wall after plaque rupture and disadvantageous because it may lead to vasospasm and to the progression of atherosclerosis.
Keywords: plaque rupture